Development of Electrically Conductive Double‐Network Hydrogels via One‐Step Facile Strategy for Cardiac Tissue Engineering. Issue 4 (2nd December 2015) - Yang, Boguang; Yao, Fanglian; Hao, Tong; Fang, Wancai; Ye, Lei; Zhang, Yabin; Wang, Yan; Li, Junjie; Wang, Changyong
Abstract : Cardiac tissue engineering is an effective method to treat the myocardial infarction. However, the lack of electrical conductivity of biomaterials limits their applications. In this work, a homogeneous electronically conductive double network (HEDN) hydrogel via one‐step facile strategy is developed, consisting of a rigid/hydrophobic/conductive network of chemical crosslinked poly(thiophene‐3‐acetic acid) (PTAA) and a flexible/hydrophilic/biocompatible network of photo‐crosslinking methacrylated aminated gelatin (MAAG). Results suggest that the swelling, mechanical, and conductive properties of HEDN hydrogel can be modulated via adjusting the ratio of PTAA network to MAAG network. HEDN hydrogel has Young's moduli ranging from 22.7 to 493.1 kPa, and its conductivity (≈10 −4 S cm −1 ) falls in the range of reported conductivities for native myocardium tissue. To assess their biological activity, the brown adipose‐derived stem cells (BADSCs) are seeded on the surface of HEDN hydrogel with or without electrical stimulation. Our data show that the HEDN hydrogel can support the survival and proliferation of BADSCs, and that it can improve the cardiac differentiation efficiency of BADSCs and upregulate the expression of connexin 43. Moreover, electrical stimulation can further improve this effect. Overall, it is concluded that the HEDN hydrogel may represent an ideal scaffold for cardiac tissue engineering. Abstract : A homogeneous electrically conductive double‐network hydrogel, containing poly(thiophene‐3‐acetic acid) (PTAA) network and methacrylated aminated gelatin (MAAG) network, is prepared by a one‐step strategy. The hydrogels have good mechanical properties and electrical conductivity. Their swelling behaviors can be modulated via adjusting the ratio of PTAA/MAAG. Moreover, they can improve the proliferation and cardiac differentiation efficiency of brown adipose‐derived stem cells.